THE ROLE AND IMPORTANCE OF A COMPLIANCE OFFICER IN THE ACTIVITIES OF A FINANCIAL INSTITUTION IN ORDER TO PREVENT THE LEGALIZATION (LAUNDERING) OF CRIMINALLY ACQUIRED FUNDS AND THE FINANCING OF TERRORISM - Kalinina, Suzanna (Administrative and Criminal Justice, 2021)
The relevance of the topic is confirmed by the changes taking place in the financial monitoring system: the complication of procedures aimed at countering money laundering and financing of terrorism, the creation of specialized international and European requirements and the changes of requirements for compliance specialists. Financial institutions more often face the incompetence the incompetence of these employees and their negligence. The author analysed anti money laundering and counter financing of terrorism legal acts, as well as revealed the main recommendations to financial institutions for preventing money laundering and terrorism financing. Based on scientific research, the main risk factors for using financial institutions for money laundering were identified. Based on these risks factors, the author identified the role and importance of a compliance officer in order to prevent the legalization (laundering) of criminally acquired funds and the financing of terrorism.